2014
DOI: 10.1007/s00384-014-1939-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported recovery after enhanced colorectal cancer surgery: a longitudinal six-month follow-up study

Abstract: 1 AbstractPurpose. The concept of enhanced recovery after surgery (ERAS) is a modern regime of care, and numerous studies have proved its beneficial impact on recovery after colorectal surgery. However, little is known about patients' continuing recovery after discharge. Therefore, the purpose of this study was to describe patientreported recovery after colorectal cancer surgery in the context of ERAS from the day of discharge until one month and six months after surgery.Method. Assessments were made at discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Lithner, Klefsgard, Johansson, and Andersson () inform that patients expressed a need for information about how to handle both the physical and emotional challenges after being discharged from hospital. Other research confirms that the pattern of recovery, as well as the time needed to reach the state of being fully recovered, depends on the individual (Jakobsson, Idvall, & Wann‐Hansson, ).…”
Section: Introductionmentioning
confidence: 78%
“…Lithner, Klefsgard, Johansson, and Andersson () inform that patients expressed a need for information about how to handle both the physical and emotional challenges after being discharged from hospital. Other research confirms that the pattern of recovery, as well as the time needed to reach the state of being fully recovered, depends on the individual (Jakobsson, Idvall, & Wann‐Hansson, ).…”
Section: Introductionmentioning
confidence: 78%
“…This was based on previous research by Jakobsson et al (2014), which showed differences between types of surgical procedures in terms of length of surgery, blood loss and length of hospital stay, but also a variety in recovery. This was based on previous research by Jakobsson et al (2014), which showed differences between types of surgical procedures in terms of length of surgery, blood loss and length of hospital stay, but also a variety in recovery.…”
Section: Limitationsmentioning
confidence: 99%
“…It is also known that the tumour's location causes different postoperative outcomes and long-term symptoms related to the surgical procedure (Wilson et al 2006, Di Fabio et al 2008, Jansen et al 2010, Caravati-Jouvenceaux et al 2011, Jakobsson et al 2014). It is also known that the tumour's location causes different postoperative outcomes and long-term symptoms related to the surgical procedure (Wilson et al 2006, Di Fabio et al 2008, Jansen et al 2010, Caravati-Jouvenceaux et al 2011, Jakobsson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study by Jakobsson et al (2014), patients after an APR procedure showed a significant deterioration in recovery 1 month after surgery regarding the PRP items fatigue, muscle weakness, and feeling down. In a previous study by Jakobsson et al (2014), patients after an APR procedure showed a significant deterioration in recovery 1 month after surgery regarding the PRP items fatigue, muscle weakness, and feeling down.…”
Section: Discussionmentioning
confidence: 81%